2023
DOI: 10.1177/21582440231174355
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Efficiency of the Lecture Method and Flipped Classroom Instruction Method on EFL Students’ Academic Passion and Responsibility

Abstract: In recent years, there has been an increasing interest in the efficiency of the lecture and flipped classroom instruction method (FCIM) on EFL students’ academic passion (AP) and responsibility. Although these variables have been studied before, more studies still need to be conducted in this field. The statistical population of this study includes all language students at the University of Tabriz in the academic year 2022–2023. In the current study, 72 of 552 persons were selected using a one-stage cluster sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…FL offers students the opportunity to learn at their own pace and provides a variety of in-class activities that support active learning strategies, including peer interaction, active learning, and cooperative learning Liu et al, 2023;Zhou et al, 2023). This instructional approach fosters flexibility and student engagement, offering a diverse learning experience that extends beyond traditional classroom methods (Divjak et al, 2022;Senali et al, 2022;Tambunan et al, 2022).…”
Section: Flipped Learningmentioning
confidence: 99%
“…FL offers students the opportunity to learn at their own pace and provides a variety of in-class activities that support active learning strategies, including peer interaction, active learning, and cooperative learning Liu et al, 2023;Zhou et al, 2023). This instructional approach fosters flexibility and student engagement, offering a diverse learning experience that extends beyond traditional classroom methods (Divjak et al, 2022;Senali et al, 2022;Tambunan et al, 2022).…”
Section: Flipped Learningmentioning
confidence: 99%
“…However, many researchers believe that classroom lectures are an inefficient method of helping students acquire the necessary knowledge and skills, and they criticise it for this reason (Gilboy et al, 2015). Research into disengaged students identified that this transmission model of instruction induced passivity and boredom in the students (Liu et al, 2023;Marks, 2000). In contrast, studentcentred learning is where teachers function more as coaches than lecturers, allowing students a say in their education and personalising instruction so they can learn at their own pace (Kamali, 2023).…”
Section: Introductionmentioning
confidence: 99%